The Influence of Intensity of Accessing PT KAI’s Instagram Account @daop6yk on Followers’ Fulfillment of Information Needs - Suciati; Zulianto, Nabila Fara Anjani (Jogjakarta Communication Conference (JCC), 2023)
This study aims to explain how much influence the intensity of accessing an Instagram account has on the followers' fulfillment of information needs. This study's population consisted of 100 Instagram followers of the Instagram account @daop6yk. The sampling technique used convenience sampling technique. The primary data was collected using a questionnaire that has undergone validity and reliability testing. The validity test was tested through the Pearson Product Moment formula, while the reliability test used Cronbach's Alpha method. Data analysis in this study used a simple linear regression analysis method. The study's findings indicate that the intensity of access positively influences the fulfillment of information needs. This is indicated by the t count of 10,889 and a significance value of 0,000 <0,05. The coefficient of determination (R2) is 0,533 or 53,3%. Thus, it can be concluded that the intensity of accessing PT KAI's Instagram account @daop6yk can influence 53,3% of followers' fulfillment of information needs, while the remaining 46,7% is influenced by other factors not examined in this study. Other factors that can influence followers’ fulfillment of information needs are demographic, role-related, and environment.